Analysis of peroxidase activity in diabetic retinopathy and in applying various corrective means - Ya. V. Sirman; I. V. Savytskyi (Journal of Education, Health and Sport, 2019)
Hyperglycemia stimulates the development of oxidative stress, which in turn is a powerful pathophysiological mechanism for the development of microvascular complications in diabetes. Increased production of reactive oxygen species is observed both during development and during the progression of diabetic retinopathy. The study was performed on white Wistar rats weighing 180-200 g. According to the tasks, the animals were divided into 7 groups: 1st group - 60 intact animals; Group 2 - 60 animals in which diabetic retinopathy was simulated without further correction. Group 3 - 60 animals, which simulated diabetic retinopathy with subsequent correction of hyperglycemia; Group 4 - 60 animals in which diabetic retinopathy was simulated with subsequent correction of hyperglycemia, administration of aflibercept and L-arginine solution; Group 5 - 60 animals in which diabetic retinopathy was simulated with subsequent correction of hyperglycemia, administration of aflibercept and bromfenac; Group 6 - 60 animals in which diabetic retinopathy was simulated with subsequent correction of hyperglycemia, administration of aflibercept, L-carnitine and bromfenac; Group 7 - 60 animals, which simulated diabetic retinopathy with subsequent correction of hyperglycemia, the introduction of aflibercept, a solution of L-arginine and citicoline. The results indicate the development of oxidative stress from the 30th and with subsequent progression on the 60th and 180th days of experimental diabetic retinopathy, which is confirmed by a decrease in peroxidase activity in the 2nd group, the maximum of which is observed in the 3rd stage. Correction with hypoglycemic agents in group 3 had a positive effect, but was not able to restore the activity of the antioxidant enzyme, so there was a need for additional drugs. The use of aflibercept and nitric oxide donor in group 4 to correct the development of diabetic retinopathy had a positive effect on increasing the activity of peroxidase, which peaked on the 180th day of the experiment, but did not reach the control values. The combined administration of bromfenac and aflibercept in group 5 was shown to significantly increase antioxidant activity, but not as significantly as in group 4. Administration of aflibercept, L-carnitine, and bromfenac to group 6 animals was shown to restore antioxidant protection as early as day 30 and was continued on days 60 and 180 of the study, but the results did not reach control values. The combination of metformin, aflibercept, L-arginine and citicoline in rats of the 7th group proved to be the most effective correction, as evidenced by the normalization of peroxidase activity on the 30th and 60th day of the experiment, and on the 180th recovery of marker activity to control values was recorded.